Improved model for the establishment and evaluation of detrusor overactivity in female Wistar rats - Nian-zhao Zhang; Lin Ma; Jian-bo Zhang; Jun Chen (International Brazilian Journal of Urology, 2014)
Objective To improve the model for establishment and evaluation of detrusor overactivity in female Wistar rats. Materials and Methods We ligated the perineal urethra of female Wistar rats and then performed filling cystometry. The probability of detrusor overactivity, bladder capacity, peak voiding pressure and histological changes were investigated. Results Detrusor overactivity ratio of the obstruction group was 32.4%. Bladder capacity increased from 0.273 ± 0.036mL in control group to 0.89 ± 0.19mL in detrusor overactivity group (P < 0.001), and peak voiding pressure increased from 45.9 ± 4.1 cm.H2O to 63.5 ± 17.4cm.H2O (P = 0.007). For obstruction group, compared to no detrusor overactivity rats, detrusor overactivity rats had higher bladder capacity (0.89 ± 0.19mL versus 0.43 ± 0.09mL, P < 0.001) and higher peak voiding pressure (63.5 ± 17.4cm.H2O versus 44.8 ± 6.2cm.H2O, P = 0.005). Detrusor overactivity rats were classified according to peak voiding pressure (49.2 ± 4.2cm.H2O versus 80.8 ± 7.1cm.H2O, P < 0.001). Moreover, bladder weight increased significantly in detrusor overactivity rats (P = 0.003, P = 0.028) and detrusor histological hypertrophy was observed. Conclusions Ligating perineal urethra and filling cystometry with intra-urethral cannula approach is a simple and easily reproducible method to establish and evaluate the model of detrusor overactivity in rats.